Inflammatory response of skin autografting in the chicken - SHRIVASTAVA, A B; VEGAD, J L; KATIYAR, A K (The Indian Journal of Animal Sciences, 2013)
Pathology of skin autografting in the chicken showed grossly cyanosis and oedema in the beginning. Histopathologically, endothelial swelling and vascular wall degeneration. endothelia swelling and spongiosis, and focal degeneration. were observed. These changes were gradually reduced and the graft appeared healthier at seventh day. The vascular and cellular changes conformed with the pattern of reaction in the chicken in response to incised wounding. Noteworthy finding was the formation of prominent perivascular lymphoid aggregates.